The Concepts of Al-Farabi in Education: it's Implications in Learning Arabic - Frida Akmalia Frida Akmalia; Sofyan Sauri Sofyan Sauri (Attanwir : Jurnal Keislaman dan Pendidikan, 2020)
In this article, we focus on the concepts of Al-Farabi in education, and it's implications in learning Arabic. We use a descriptive approach in this article by gathering data about the thoughts of Al-Farobi. The researchers are investigating, identifying, explaining, and predicting a prevalent phenomenon based on the data collected in the field. We use a literature analysis in the study technique by reading and understanding books, records, or other written sources, which are essential and help the thoughts of Al-Farobi. The methodology of data analysis is qualitative techniques of data analysis. In this article is known that: First, Al-Farabi was best known as Abu Nasr among Latinos of the Middle-Century. He is muslim figure who has great attention to education. Second, the concepts of Al-Farabi for educational purposes is guiding the individual towards perfection. And Third, there are philosophical, theoretical-pedagogical, and practical implications of Al-Farabi's educational concepts in learning Arabic.